Rectal Neuroendocrine Tumor With Non‐Atypical Mucous Cell Glands: A Case Report - Akira Ishikawa; Hidenori Tanaka; Ken Yamashita; Shiro Oka; Shinji Mii (JGH Open)
ABSTRACT Introduction Neuroendocrine neoplasms (NENs) of rectal origin containing non‐neuroendocrine components are extremely rare. Additionally, there have been no previous reports of NENs accompanied by nonmalignant components. Herein, we report a case of an NEN accompanied by mucous cell glands that could not be regarded as a carcinoma. Case Presentation A Japanese woman in her 30s underwent a colonoscopy that revealed a yellowish submucosal tumor‐like protrusion in the rectum. Endoscopic findings suggested a high possibility of NEN; therefore, endoscopic mucosal resection was performed. Histopathologically, it was found that tumor cells had invaded beyond the muscularis mucosa into the submucosa. The tumor predominantly consisted of neuroendocrine tumor (NET) components with mucous cell glands observed in 5% of the tumor. The mucous cell glands were Periodic acid‐Schiff‐positive and immunohistochemically positive for CK20, whereas synaptophysin, CD56, and chromogranin A were negative. Based on the above findings, the pathological diagnosis was NET G1 with mucous cell glands. Conclusion This is the first reported case worldwide. Further discussion is needed to address the atypical nature of the glandular component and explore the differences and similarities with entities such as mixed neuroendocrine–non‐NENs.